Comparison of the initial ovarian response, the synchrony of oestrus and ovulation and chronic stress response after administration of 100 or 250 μg of GnRH to randomly cycling Bos indicus cattle. Issue 10 (28th June 2022) - Abdallah, M; Joone, C; Edwards, S; Das, S; Cavalieri, J
Abstract : Objective: This study investigated the effects of administering saline, 100 or 250 μg of gonadotrophin releasing hormone (GnRH) on ovarian response, synchrony of oestrus and ovulation and chronic stress response in Bos indicus cattle. Design: Randomised control. Methods: Animals were either left untreated (n = 20) or on day 0 treated with an intravaginal progesterone releasing device and either saline (n = 24), 100 μg (n = 35), or 250 (n = 35) μg of GnRH, intramuscular (IM). Blood was sampled 1.4 h after administration of treatment to monitor concentrations of luteinising hormone (LH) and P4 in serum and again 5 days later. On day 5 intravaginal P4 releasing device were removed, cloprostenol was administered IM and again 8 h later. Oestrus and ovulation were then monitored with ultrasonography for 6.5 days. Hair was clipped on day 55 for analysis of hair cortisol concentrations (HCC). Results: No significant differences were found between Saline and GnRH treatments in the odds of inducing a new corpus luteum (CL) and the synchrony of oestrus or ovulation. HCC did not differ significantly between treatments. Mean concentrations of LH in serum on day 0 were less in the Saline compared to 100 and 250 μg GnRH treatments but did not differ between different doses of GnRH. Conclusion: Mean concentrations of LH and the odds of inducing a new CL were not increased after administering 250 μg compared to 100 μg of GnRH. Animal handling events in the study did not influence HCC. Further research is needed to better optimise responses to GnRH in B . indicus cattle.